Classical celiac disease is more frequent with a double dose of HLA-DQB1*02: A systematic review with meta-analysis. - Judit Bajor; Zsolt Szakács; Nelli Farkas; Péter Hegyi; Anita Illés; Margit Solymár; Erika Pétervári; Márta Balaskó; Gabriella Pár; Patrícia Sarlós; Ákos Szűcs; József Czimmer; et al. (PLoS ONE, 2019)
Background and aims Experimental data suggest that the HLA-DQ2 gene dose has a strong quantitative effect on clinical outcomes and severity of celiac disease (CD). We aimed to conduct a meta-analysis with systematic review to investigate the association between HLA-DQB1*02 gene doses and the characteristics of CD. Methods We searched seven medical databases for studies discussing HLA-DQB1 gene dose in CD and various disease characteristics, such as clinical presentation, histology, age at diagnosis, and comorbidities. Odds ratios (OR, for categorical variables) and weighted mean differences (for age) were calculated to compare patients with a double dose of HLA-DQB1*02 versus those with single and zero doses. Heterogeneity was tested with I2-statistics and explored by study subgroups (children and adults). Results Twenty-four publications were eligible for meta-analysis. Classical CD was more frequent with a double versus single dose of the HLA-DQB1*02 allele (OR = 1.758, 95%CI: 1.148-2.692, I2 = 0.0%). In pediatric studies, gene dose effect was more prominent (OR = 2.082, 95%CI: 1.189-3.646, I2 = 0.0% and OR = 3.139, 95%CI: 1.142-8.630, I2 = 0.0% for the comparisons of double versus single and double versus zero dose, respectively). Atrophic histology was more prevalent with a double versus zero dose (OR = 2.626, CI: 1.060-6.505, I2 = 21.3%). We observed no gene dose effect regarding diarrhea, age at diagnosis, the severity of villous atrophy, and the association with type 1 diabetes mellitus. Conclusion A double dose of HLA-DQB1*02 gene seems to predispose patients to developing classical CD and villous atrophy. Risk stratification by HLA-DQB1*02 gene dose requires further clarification due to the limited available evidence.